Cumulative live birth rate prognosis based on the number of aspirated oocytes in previous ART cycles. Issue 1 (12th December 2018) - Malchau, S S; Henningsen, A A; Forman, J; Loft, A; Nyboe Andersen, A; Pinborg, A
Abstract: STUDY QUESTION: Is the number of aspirated oocytes in the first ART cycle associated with the cumulative live birthrates (CLBR) in subsequent cycles? SUMMARY ANSWER: The number of aspirated oocytes in the first cycle was associated with CLBR in subsequent cycles. Previous treatment response predicts outcome in future cycles. WHAT IS KNOWN ALREADY: Previous reports have shown a positive association between the number of retrieved oocytes and live birthrate per fresh treatment cycle. This has also been shown for the CLBR in one complete ART-cycle, including possible subsequent frozen–thawed transfers (FER). It has been shown that women with less than five oocytes in the first cycle have poorer outcome within six complete cycles than women with more than 12 oocytes, suggesting that the number of aspirated oocytes in the first cycle may be reproduced in later cycles. However, other studies have shown that an initial low treatment response may be improved with increased gonadotrophin start-dose. STUDY DESIGN, SIZE, DURATION: The Danish National IVF-registry includes all ART treatments in public and private clinics since 1994. Treatment-cycles were cross-linked with the Medical Birth Registry, identifying treatment-related births and natural conception births. This national cohort study includes all women starting ART treatments with homologous eggs between 2002 and 2011, N = 30 486. Subjects were followed for up to four fresh ART-cycles including subsequent FER-cycles (=four complete cycles), until the first livebirth, or until December 2011. PARTICIPANTS/MATERIALS, SETTING, METHODS: The CLBR within 1–4 complete ART-cycles were calculated as the proportion of women with a livebirth, out of all women initiating ART-treatment, including drop-outs (no livebirth or no continued treatment within follow-up). In women with one year follow-up from last treatment, multivariate logistic regression analysis assessed impact of retrieved oocytes on CLBR, adjusting results for female age and cause of infertility. Hospital admission due to ovarian hyperstimulation syndrome (OHSS) was reported. MAIN RESULTS AND THE ROLE OF CHANCE: After one, two and three complete ART-cycles, the CLBRs attributable to ART treatment were 26.4% [95%CI 25.9–26.9], 42.6% [42.0–43.1] and 51.3% [50.7–51.9], respectively. The CLBR attributable to non-ART related conception (natural conception or intrauterine insemination) were 5.3% [5.0–5.6], 8.3% [8.0–8.7] and 10.6% [10.3–11.0], after one, two and three complete cycles. In women without a live birth in the first complete cycle, the number of aspirated oocytes predicted the outcome in the second and third cycle: When compared to women with 0–3 aspirated oocytes in the first cycle, the odds for live birth in the second and third cycle was 1.18 [1.07–1.30] for women with 4–9 aspirated oocytes in the first cycle, 1.41 [1.27–1.57] for women with 10–15 aspirated oocytes and 1.63 [1.42–1.88] for women with more than 15 aspirated oocytes. For women without a livebirth in the first and second cycle, the sum of aspirated oocytes predicted outcome in the third complete cycle. Women with a sum larger than six aspirated oocytes, had marked increased odds ratios for livebirth in the third complete cycle, compared to women with a sum of 0–6 oocytes in the first and second fresh cycle. Incidence of hospital-admission due to OHSS was 1.7% in the first cycle, decreasing to 1.3% and 1.0% in the second and third cycles. LIMITATIONS, REASONS FOR CAUTION: Although mandatory, there may be treatment-cycles not registered in the IVF-registry. Missing information in number of aspirated oocytes are most likely random losses of information. There were few observations in women with more than 15 aspirated oocytes and these birthrates should be interpreted cautiously. Information on gonadotrophin dose used for stimulation was not available, nor was information on dose adjustments in subsequent cycles. WIDER IMPLICATIONS OF THE FINDINGS: With these results we can counsel couples returning for fertility treatments, providing an age-stratified revised prognosis for chances of live birth and risk of OHSS, reflecting prior failed attempts and previous ovarian response. STUDY FUNDING/COMPETING INTEREST(S): This study was unconditionally funded by Ferring Pharmaceuticals and ReproUnion. The funders had no role in the study design, data collection and interpretation, or decision to submit the work for publication. The authors have no conflicts of interest. TRIAL REGISTRATION NUMBER: The study was approved by the Danish Data Protection Agency (J.nr. 2012-41-1330).